Triceps Surae Muscle Architecture Adaptations to Eccentric Training - Geremia, Jeam Marcel; Baroni, Bruno Manfredini; Bini, Rodrigo Rico; Lanferdini, Fabio Juner; de Lima, Amanda Rodrigues; Herzog, Walter; Vaz, Marco Aurélio (Frontiers in Physiology, 2019)
Background: Eccentric exercises have been used in physical training, injury prevention and rehabilitation programs. The systematic use of eccentric training promotes specific morphological adaptations on skeletal muscles. However, synergistic muscles, such as the triceps surae components, might display different structural adaptations due to differences in architecture, function and load sharing. Therefore, the purpose of this study was to determine the effects of an eccentric training program on the triceps surae (gastrocnemius medialis - GM, gastrocnemius lateralis - GL, and soleus - SO) muscle architecture. Methods: Twenty healthy male subjects (26±4 years) underwent a 4-week control period followed by a 12-week eccentric training program. Muscle architecture (fascicle length, pennation angle, and muscle thickness) of GM, GL and SO was evaluated every four weeks by ultrasonography. Results: Fascicle lengths (GM: 13.2%; GL: 8.8%; SO: 21%) and muscle thickness increased (GM: 14.9%; GL: 15.3%; SO: 19.1%) from pre- to post-training, whereas pennation angles remained similar. GM and SO fascicle length and muscle thickness increased up to the 8th training week, whereas GL fascicle length increased up to the 4th week. SO displayed the highest, and GL the smallest gains in fascicle length post-training. Conclusion: All three synergistic plantar flexor muscles increased fascicle length and muscle thickness with eccentric training. Muscle thickness increased similarly among the synergistic muscles, while the muscle with the shortest fascicle length at baseline (SO) showed the greatest increase in fascicle length.